The family Juncaceae in Mexico - Balslev, Henrik; Duno de Stefano, Rodrigo (Instituto de Ecología, A.C., 2015)
A treatment of the family Juncaceae Juss. for the flora of Mexico is presented. The family includes two genera in this country: Juncus L. andLuzula DC. The first genus consists of 31 species and the second one of five. Keys for identification of the taxa, morphological descriptions, taxonomic notes, and information about the geographic distribution are provided, as well as some illustrations. One species is endemic:Juncus chiapasensis Balslev occurs only in the state of Chiapas. A second species, J. textilis Buchenau, is a local endemism, occurring in the state of Baja California as well as in the state of California in the United States of America.